2021
DOI: 10.1080/23311886.2021.1913848
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce the exclusion of children with disabilities from education: A Zimbabwean perspective from the field

Abstract: Access to education is a fundamental human right. However, children with disabilities in most African countries (including Zimbabwe) are often excluded and marginalized. They persistently face barriers to the enjoyment of their basic human rights and inclusion in education. This paper sought to examine some interventions being employed by stakeholders to enhance the inclusion of children with disabilities in schools. The study covered five districts in Zimbabwe using a mixed-methods design. Study findings reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…It was revealed that the adverse comments resulted in physically challenged learners developing negative attitude towards Art and Design. The findings are consistent with the results of the study carried out in Zimbabwe by Dube, Ncube, Mapuvire, Ndlovu, Ncube and Mlotshwa, (2021) that deleterious attitudes and stereotypes towards learners with disabilities hinder their access to quality education. However, it came out that some physically challenged learners were confident in Art and Design work despite the negative comments.…”
Section: Discussionsupporting
confidence: 91%
“…It was revealed that the adverse comments resulted in physically challenged learners developing negative attitude towards Art and Design. The findings are consistent with the results of the study carried out in Zimbabwe by Dube, Ncube, Mapuvire, Ndlovu, Ncube and Mlotshwa, (2021) that deleterious attitudes and stereotypes towards learners with disabilities hinder their access to quality education. However, it came out that some physically challenged learners were confident in Art and Design work despite the negative comments.…”
Section: Discussionsupporting
confidence: 91%
“…In similar fashion, Dube et al (2021) proffer that the social model is conscientised by policy and system factors which focuses on discriminatory policies that segregate the disabled students from participating in education; social and community factors which involve communal stigma and negative attitude of the family towards children with disability hence depriving them of accessing education; school environment which suggests that children with disability face discrimination and stigma, not because of impairment, but the environment, including the one involved in education. Alternatively, the social model focuses on how the barriers that hinder the disabled people's participation can be remedied (Pfeiffer, 2003).…”
Section: Theoretical Perspective On Disabilitymentioning
confidence: 99%
“…There continues to be a widespread belief that disability is caused by supernatural forces, such as avenging spirits, witchcraft, or punishment from God or the ancestors (Mukushi et al, 2019;Nkomo et al, 2020). When disabilities are present from birth, mothers are often held responsible (Nkomo et al, 2020), possibly due to the belief that the disability is a punishment for infidelity (Dube et al, 2021). These notions of spiritual or moral "contamination" are often linked with stigma toward children with disabilities and their families (van der Mark and Verrest, 2014), which can contribute to a break-down in communal support (van der Mark and Verrest, 2014;Mukushi et al, 2019) that leaves many parents feeling overwhelmed by their caregiving role and experiencing clinical distress (Dambi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%